2021
DOI: 10.1007/s00216-021-03710-z
|View full text |Cite
|
Sign up to set email alerts
|

Activatable MRI probes for the specific detection of bacteria

Abstract: Activatable fluorescent probes have been successfully used as molecular tools for biomedical research in the last decades. Fluorescent probes allow the detection of molecular events, providing an extraordinary platform for protein and cellular research. Nevertheless, most of the fluorescent probes reported are susceptible to interferences from endogenous fluorescence (background signal) and limited tissue penetration is expected. These drawbacks prevent the use of fluorescent tracers in the clinical setting. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Specifically, biosensors based on nuclease-activatable oligonucleotides have been used to detect various conditions [133] such as infections [70,134,135] and cancer [67][68][69].…”
Section: Oligonucleotides: Substrates Of Nucleasesmentioning
confidence: 99%
“…Specifically, biosensors based on nuclease-activatable oligonucleotides have been used to detect various conditions [133] such as infections [70,134,135] and cancer [67][68][69].…”
Section: Oligonucleotides: Substrates Of Nucleasesmentioning
confidence: 99%
“…Currently, the direct labeling of pathogens in the infection sites by imageable probes has been used to detect bacterial infections by performing in vivo bioimaging, which provides an intuitive and feasible solution for infection diagnosis and treatment. [155][156][157] Gram-negative bacteria, such as Enterobacterales, can cause severe, deep-seated infections, often leading to sepsis or even death. To create a non-invasive whole-body analysis tool that can specifically locate pathogens, Jain's group constructed a PET imaging probe on the basis of 18 F-FDS, and found that such probes could selectively distinguish Enterobacterales infection from other pathologies in mice by PET signal detection.…”
Section: Diagnosis Of Bacterial Infectionsmentioning
confidence: 99%
“…Currently, the direct labeling of pathogens in the infection sites by imageable probes has been used to detect bacterial infections by performing in vivo bioimaging, which provides an intuitive and feasible solution for infection diagnosis and treatment. [ 155–157 ]…”
Section: Applications Of Bacteria‐based Living Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, gadolinium oxide and superparamagnetic iron oxide complexes have been successfully applied in tumor cell imaging based on the change of their spacing after cleavage of the linker, restoring the T 1 -weighted MRI signal . This nanoscale distance-dependent phenomenon between paramagnetic “enhancer” and superparamagnetic “quencher” was later defined as magnetic resonance tuning (MRET), that is, the enhancer and the quencher are separated, resulting in a stronger T 1 MRI signal (ON state) due to the accelerated water proton relaxation by the electron spin fluctuation of the enhancer, while the enhancer and the quencher are close enough to each other, resulting in a low T 1 MRI signal (OFF state) due to the slowed water proton relaxation. , This MRET phenomenon has been employed to develop imaging contrast for imaging enzymes, sepsis, epilepsy, infection, and tumors. As for MRET-based tumor imaging, different MRET probes were constructed and proved to have enhanced imaging signals compared with traditional MRI contrast. However, the reported work rarely involves the early detection of tumors, which is essential to improving the cure rate of tumors.…”
mentioning
confidence: 99%